Analysing Financial Market Integration between Stock and Precious Metals Indices - Manuel, Áureo; Dias, Rui; Galvão, Rosa; Varela, Miguel (International Journal of Economics and Financial Issues, 2024)
Given the global pandemic in 2020 and the Russian invasion of Ukraine in 2022, there is renewed interest in understanding the integration between the Dow Jones (United States), Amman SE General (Jordan), BLSI (Lebanon), EGX 30 (Egypt), ISRAEL TA 125 (Israel), MASI (Morocco), MOEX (Russia) stock indices and the precious metals Gold Bullion LBM, Silver, Handy & Harman, London Platinum, in the period from 1 January 2018 to 23 November 2023. The study aims to address two key questions: i) Have the events of 2020 and 2022 influenced the integration between the capital markets of MENA countries and precious metals? ii) In the case of a significant increase in integration, will this imply a trend towards efficiency or inefficiency in the markets analysed? The results of the cointegration tests show an increase in integrations between the Tranquil and Stress subperiods; for example, platinum rose from zero integrations to 4, being the market most affected by the events of 2020 and 2022, the MOEX increased from 3 to 6 integrations, the Dow Jones index rose from 1 to 3 integrations, the Amman SE General from 1 to 2 integrations. On the other hand, the ISRAEL TA 125 index decreased from 5 integrations in the Calm period to 1 integration during the Stress period. The EGX also decreased from 2 integrations to one integration, the MASI from three to zero integrations, and gold from 1 integration to zero. The BLSI stock index maintained its 1-1 level of integrations, while silver also followed the same 2-2 trend. These results do not allow acceptance of the first research question since it was found that there were increases/decreases in integrations during the 2020 and 2022 events. The DFA slopes were estimated to answer the second research question since most markets showed significant persistence. However, it was found that this persistence did not coincide with an increase/decrease in the level of integration between the markets analysed. Given these results, the second research question was also partially rejected. In conclusion, the results of this study have significant implications for international investors operating in the financial markets of MENA countries.